IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH - Muhammad Mubaroh; Alben Ambarita; Irawan Suntoro (Program Studi Magister Manajemen Pendidikan)
The purpose of this study was to determine and describe: 1) Planning academic supervision; 2) Implementation of the academic supervision; 3) Evaluation of the principal supervision; 4) Improved pedagogical competence; 5) The response of teachers to the academic supervision. This study used a qualitative approach with a case study approach. The results of this study indicate that: 1) Supervision in order to improve teachers pedagogical competence; 2) The principal implementing academic supervision with view technics; 3) evaluation after supervision, 4) there is positive response to the supervision, 5) pedagogical competencies that teachers need is the ability to make curriculum and learning materials, lesson plan preparation, implementation of learning, assessing learning outcomes.Tujuan dari penelitian ini adalah untuk mengetahui dan mendeskripsikan: 1) Perencanaan supervisi akademik; 2) Pelaksanaan supervisi akademik; 3) Evaluasi pengawasan Kepala Sekolah; 4) Peningkatan kompetensi pedagogik; 5) Respon guru terhadap supervisi akademik. Penelitian ini menggunakan pendekatan kualitatif dengan pendekatan studi kasus. Hasil penelitian ini menunjukkan bahwa: 1) Pengawasan dalam rangka meningkatkan kompetensi pedagogik guru; 2) Kepala sekolah melaksanakan supervisi akademik dalam beberapa cara; 3) evaluasi setelah pengawasan, 4) ada respon yang positif terhadap pengawasan, 5) kompetensi pedagogis yang diperlukan guru adalah kemampuan untuk membuat kurikulum dan bahan pembelajaran, penyusunan RPP, pelaksanaan pembelajaran, menilai hasil belajar.Kata kunci: evaluasi, kompetensi akademik, supervisi akademik